Preparative high-performance liquid chromatography of minor products of Streptomyces cinnamonensis - Beran, M; Nĕmecek, J; Tax, J; Zima, J; Matĕjů, J; Sajdl, P (Folia microbiologica, 1990)
Analytical and preparative high-performance liquid chromatography of 3 phenazines and furonaphthoquinone derivative on reversed-phase column are described. The mobile phase was methanol and water. The injected amount of the mixture was about 30 mg for a preparative chromatographic run requiring 80 min. Substances were detected directly in the column effluent by UV detection.
Keywords: Chromatography, High Pressure Liquid; furany; Furans; fenaziny; naftochinony; Phenazines; vysokoúčinná kapalinová chromatografie; Naphthoquinones; Streptomyces